State space mixed models for longitudinal obsservations with binary and binomial responses - Claudia Czado; Peter X.-K. Song (Ludwig-Maximilians-Universität München, Sonderforschungsbereich 386 - Statistische Analyse diskreter Strukturen, 2006)
We propose a new class of state space models for longitudinal discrete response data where the observation equation is specified in an additive form involving both deterministic and random linear predictors. These models allow us to explicitly address the effects of trend, seasonal or other time-varying covariates while preserving the power of state space models in modeling serial dependence in the data. We develop a Markov chain Monte Carlo algorithm to carry out statistical inference for models with binary and binomial responses, in which we invoke de Jong and Shephards (1995) simulation smoother to establish an efficient sampling procedure for the state variables. To quantify and control the sensitivity of posteriors on the priors of variance parameters, we add a signal-to-noise ratio type parameter in the specification of these priors. Finally, we illustrate the applicability of the proposed state space mixed models for longitudinal binomial response data in both simulation studies and data examples.
urn:nbn:de:bvb:19-epub-1868-5
Keywords: 519; Longitudinal data; Markov chain Monte Carlo; probit; random effects; regression; seasonality; signal-to-noise ratio; Zustandsraummodell; Markovscher Prozess; Monte-Carlo-Methode; Probit-Modell; Regression; Saisonbereinigung; Theorie